Exchange and Communal Orientations (ECO) scale: The construction and validation of a method to measure target-specific relational orientations - Agata Gasiorowska; Anna O. Kuzminska; Tomasz Zaleskiewicz (PLoS ONE, 2025)
This paper introduces the ECO Scale—a novel self-report measure to assess the degree to which individuals exhibit a dispositional tendency to orient themselves according to communal or exchange rules when establishing and maintaining relationships with others. In a series of six studies (total N = 3,252) conducted with diverse samples of Polish, American, and British participants, we documented that the 20-item ECO Scale in two separate language versions (English and Polish) is a psychometrically solid measure that can be used in different research settings. In Studies 1–3, we demonstrated the two-dimensional structure of the scale and provided support for configural, metric, residual, and partial scalar invariance of the scale across Poland and the United States (US). Study 2 supports the discriminant and construct validity of the scale, and demonstrates gender differences across orientations. Study 3 confirmed the convergent and divergent validity of the communal and exchange dimensions. Study 4 demonstrated the high test-retest reliability of the scale. Finally, Studies 5 and 6 verified the diagnostic and predictive validity of the ECO Scale. Study 5 showed that a high level of communal orientation predicts perceptions of the ambiguous social situation as more communal, while a high level of exchange orientation predicts perceptions of the ambiguous social situation as more exchange-based. Study 6 demonstrated that relational orientations measured with the ECO Scale predicts not only the declared willingness to provide assistance in a situation characterized by purely communal, purely exchange, or conflictual communal and exchange cues, but also actual behavior in these situations.